2011
DOI: 10.1007/s00216-011-5089-x
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the LOQ in real-time PCR by receiver operating characteristic curve analysis: application to qPCR assays for Fusarium verticillioides and F. proliferatum

Abstract: Real-time PCR (qPCR) is the principal technique for the quantification of pathogen biomass in host tissue, yet no generic methods exist for the determination of the limit of quantification (LOQ) and the limit of detection (LOD) in qPCR. We suggest using the Youden index in the context of the receiver operating characteristic (ROC) curve analysis for this purpose. The LOQ was defined as the amount of target DNA that maximizes the sum of sensitivity and specificity. The LOD was defined as the lowest amount of ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
108
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(109 citation statements)
references
References 41 publications
1
108
0
Order By: Relevance
“…The spores were suspended in sterile tap water and stored at −60 °C. Rice cultures were prepared as described (Nutz et al [38]). All mycotoxins except fumonisins were extracted from 5 g rice cultures with 40 mL acetonitrile overnight with shaking, while fumonisins were extracted with methanol.…”
Section: Experimental Setup and Materialsmentioning
confidence: 99%
“…The spores were suspended in sterile tap water and stored at −60 °C. Rice cultures were prepared as described (Nutz et al [38]). All mycotoxins except fumonisins were extracted from 5 g rice cultures with 40 mL acetonitrile overnight with shaking, while fumonisins were extracted with methanol.…”
Section: Experimental Setup and Materialsmentioning
confidence: 99%
“…Quantification of F. verticillioides, F. proliferatum and F. subglutinans using Real Time PCR The primers used for the detection of F. subglutinans were Fsub565 F (TCATTGGTATGTTGTCGCTCATG) and Fsub622A R (GTGATATGTTAGTACGAATAAAGGGAGAAC), designed on the EF1g ene (Nicolaisen et al, 2009;Boutigny et al, 2012). The primers Fp3-F (CGGCCACCAGAGGATGTG) and Fp4-R (CAACACGAATCGCT TCCTGAC), designed by Jurado et al (2006) on the intergenic sequence of the ribosomal RNA gene cluster, for the detection of F. proliferatum and the primers VER1 and VER2, designed by Mulè et al, 2004 on the calmodulin gene, for the detection of F. verticilliodes, were used in Real Time as described by Nutz et al (2011); all were synthesized by PRIMM (PRIMM srl, Milan, Italy).…”
Section: Preliminary Species-specific Pcrmentioning
confidence: 99%
“…Thus, the limit of quantification (LOQ) of the FgMito assay (0.2 pg) is the equivalent of approximately five haploid cells of F. graminearum s.s. The limit of detection (LOD) corresponds to the lowest amount in a sample that can be detected with a false-negative rate below a given threshold (Nutz et al, 2011). We showed that 0.06 pg of input template could be detected with the FgMito assay, but with a 24% false negative rate only.…”
Section: Discussionmentioning
confidence: 91%